Recurrent multilocular mandibular giant cell granuloma in neurofibromatosis type 1: Evidence for second hit mutation of NF1 gene in the jaw lesion and treatment with curettage and bone substitute materials. Issue 8 (August 2016) - Friedrich, Reinhard E.; Grob, Tobias J.; Hollants, Silke; Zustin, Jozef; Spaepen, Marijke; Mautner, Victor F.; Luebke, Andreas M.; Hagel, Christian; Legius, Eric; Brems, Hilde
Abstract: Giant cell granuloma (GCG) of the jaw is a rare, well-known feature of neurofibromatosis type 1 (NF1), an inborn multisystem disorder. Recently, the development of GCG in NF1 was attributed to second hit mutations in the NF1 gene. The treatment of GCG is pragmatic with a preference for local curettage of lytic osseous areas. This report describes the surgical therapy of an NF1-affected female with multilocular mandibular GCG and hypodontia who additionally suffered from a brain tumour and Hashimoto's thyroiditis. Although local recurrence of GCG was noted, augmentation of the curetted cavities with a bone substitute in successive interventions successfully restored the extensive periradicular local defects and stabilised the teeth. A meticulous in vitro study of the GCG specimen revealed a second hit mutation in the NF1 gene in the GCG spindle-cells. This study contributes to the increasing knowledge of the molecular basis for GCG in the jaw of NF1 patients, indicating that it is a neoplasm.